2020
DOI: 10.1002/er.5985
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles spectroscopic screening of hybrid perovskite ( CH 3 CH 2 NH 3 PbI 3 ) with fundamental physical properties: A potential photovoltaic absorber

Abstract: Herein, we have discussed the ethyl-ammonium based hybrid perovskite (viz. CH 3 CH 2 NH 3 PbI 3 or EAPbI 3) as the potential candidate material for the development of photovoltaic devices having low processing cost and high power conversion efficiency (PCE). To address the stability and environmental issues due to leaching of lead from MAPbI 3 , we urge to replace cation CH 3 NH 3 + (MA +) with an appropriate cation CH 3 CH 2 NH 3 + (EA +) and hope that the EAPbI 3 perovskite would prove to be a stable and eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Therefore, the BX framework of FAPbI-12 is very close to the perfect cube. Previous studies 75–77 indicated that the structural tolerance factors of bulk APbI 3 materials with A = MA, EA, and FA are between 0.8 and 1.0, so they have high structural stability with three-dimensional perovskite structures. However, the structural tolerance factors of PAPbI 3 and BAPbI 3 are out of this range, and these two perovskites could not exist stably.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the BX framework of FAPbI-12 is very close to the perfect cube. Previous studies 75–77 indicated that the structural tolerance factors of bulk APbI 3 materials with A = MA, EA, and FA are between 0.8 and 1.0, so they have high structural stability with three-dimensional perovskite structures. However, the structural tolerance factors of PAPbI 3 and BAPbI 3 are out of this range, and these two perovskites could not exist stably.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the BX framework of FAPbI-12 is very close to the perfect cube. Previous studies [75][76][77] indicated that the structural tolerance factors of bulk APbI 3 materials with A = MA, EA, and FA are between 0.8 and 1.0, so they have high structural stability with three-dimensional perovskite structures.…”
Section: Application Of Abx-12 Cluster Models With Other A-site Cationsmentioning
confidence: 99%
“…On comparing the calculated SLME for the proposed antiperovskites with the most extensively investigated and presently being used fewer stable perovskites, we can infer that the proposed more stable antiperovskites offer the highest theoretical PCE. Furthermore, in view of SLME, the antiperovskites AsPCa 3 with SLME 34%, is expected to be a stable yet efficient photovoltaic absorber material [61,62].…”
Section: Theoretical Power Conversion Efficiencymentioning
confidence: 99%